0609 Pharmacokinetics And Formulation Selection Of Ft218, An Investigational Controlled-release Sodium Oxybate Formulation Designed For Once Nightly Dosing. (12th April 2019) - Monteith, David; Grassot, Julien; Castellan, Charlotte; Roth, Thomas
Abstract: Introduction: Sodium oxybate is indicated for the treatment of Excessive Daytime Sleepiness (EDS) and cataplexy in patients with narcolepsy. The currently marketed product, an immediate release (IR) sodium oxybate is required to be taken twice nightly: at bedtime and 2.5 to 4 hours later, thus requiring patients to awaken in the middle of the night. FT218 is an investigational controlled-release (CR) formulation of sodium oxybate intended for once nightly dosing. The pharmacokinetic performance of three prototypes of FT218 were evaluated in a PK pilot study (PKFT218-1301). Methods: Three prototypes of FT218 were manufactured by varying the polymer compositions and ratios of immediate and controlled-release microparticles. The prototypes, given as a single administration of 4.5g, were compared to IR sodium oxybate as reference, given as 2 x 2.25g, in 16 healthy volunteers. Results: Each of the three prototypes exhibited a sustained release profile with Cmax below the global Cmax of the reference drug and a C8h close to the reference values. Prototype 2 was selected for further optimization, as it exhibited PK characteristics closest to the desired target profile. This formulation exhibited a higher Cmax compared to the other prototypes (46 ± 20 (SD) µg/mL), and the AUCinf (210 ± 100 (SD) µg/ml.h) was the closest to the AUCinf of the IR formulation (214 ± 104 (SD) µg/mL.h). C8h values were 7.40 ± 5.88 (SD) µg/mL and 9.24 ± 11.77 (SD) µg/mL for prototype 2 and the reference respectively. Conclusion: The three prototypes exhibited CR profiles covering the entire night with once nightly dosing. Prototype 2, compared to the reference product, exhibited a lower overall Cmax and, importantly, a comparable C8h, while the AUC was maintained. Between subject variability of FT218 and IR sodium oxybate was comparable. If approved, FT218 could offer an important new option for the treatment of EDS and cataplexy in narcolepsy with potentially improved compliance and quality of life benefits. FT218 is currently being evaluated for efficacy in narcolepsy patients in the Phase 3 REST-ON study. Support (If Any): N/A